Biomimetic 3D Printing of Hierarchical and Interconnected Porous Hydroxyapatite Structures with High Mechanical Strength for Bone Cell Culture. Issue 1 (5th December 2018) - Song, Xiaolei; Tetik, Halil; Jirakittsonthon, Thitikan; Parandoush, Pedram; Yang, Guang; Lee, Donghee; Ryu, Sangjin; Lei, Shuting; Weiss, Mark L.; Lin, Dong
Abstract : Human bone demonstrates superior mechanical properties due to its sophisticated hierarchical architecture spanning from the nano/microscopic level to the macroscopic. Bone grafts are in high demand due to the rising number of surgeries because of increasing incidence of orthopedic disorders, non‐union fractures, and injuries in the geriatric population. The bone scaffolds need to provide porous matrix with interconnected porosity for tissue growth as well as sufficient strength to withstand physiological loads, and be compatible with physiological remodeling by osteoclasts/osteoblasts. The‐state‐of‐art additive manufacturing (AM) technologies for bone tissue engineering enable the manipulation of gross geometries, for example, they rely on the gaps between printed materials to create interconnected pores in 3D scaffolds. Herein, the authors firstly print hierarchical and porous hydroxyapatite (HAP) structures with interconnected pores to mimic human bones from microscopic (below 10 µm) to macroscopic (submillimeter to millimeter level) by combining freeze casting and extrusion‐based 3D printing. The compression test of 3D printed scaffold demonstrates superior compressive stress (22 MPa) and strain (4.4%). The human mesenchymal stromal cells (MSCs) tests demonstrate the biocompatibility of printed scaffold. Abstract : Human bone demonstrates superior mechanical properties due to its sophisticated hierarchical architecture spanning from the nano/microscopic level to the macroscopic. Herein, the authors firstly print hierarchical and porous hydroxyapatite (HAP) structures with interconnected pores to mimic human bones from microscopic to macroscopic by combining freeze casting and extrusion‐based 3D printing. The human mesenchymal stromal cells tests demonstrate the biocompatibility of printed scaffold.